MMP-2 but not MMP-9 associated with COX-2 and survival in gastric cancer. Issue 6 (26th May 2006) - Mrena, J; Wiksten, J-P; Nordling, S; Kokkola, A; Ristimäki, A; Haglund, C
Abstract : Background and aim: Matrix metalloproteinases (MMPs) MMP-2 and MMP-9 can degrade type IV collagen of extracellular matrix and basal membranes. As cyclo-oxygenase-2 (COX-2) has been shown to activate MMPs, creating one of the COX-2-promoted pathways of tumour growth and metastasis, the prognostic role of MMP-2 and MMP-9 in gastric cancer was assessed and their association with COX-2 expression was evaluated. Materials and methods: Samples were collected from 342 consecutive patients operated on for gastric cancer, of which 315 were acceptable for MMP-2, MMP-9 and COX-2 immunohistochemistry. Specimens were stained with specific antibodies, evaluated and categorised by two interpreters, and then correlated with clinical data and survival. Results: Epithelial MMP-2 immunoreactivity was associated with male sex, high stage, advanced penetration depth, non-curative surgery, high COX-2 expression and poor survival. Stromal MMP-2 expression correlated with high stage, intestinal type and non-curative surgery whereas MMP-9 correlated only with intestinal type. Stage, intent of surgery and COX-2 were independent prognostic factors. Conclusions: Epithelial MMP-2 expression in gastric cancer is associated with aggressive forms, COX-2 and poor survival, although MMP-2 was not an independent prognostic factor. In gastric cancer tumour growth is apparently induced by COX-2, and invasion is mediated by MMP-2.